2009
DOI: 10.1021/jp900737r
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the Vibrational Spectra of H5O2+ and Its Deuterium-Substituted Isotopologues by Molecular Dynamics Simulations

Abstract: In this work, we present infrared spectra of H(5)O(2)(+) and its D(5)O(2)(+), D(4)HO(2)(+), and DH(4)O(2)(+) isotopologues calculated by classical molecular dynamics simulations on an accurate potential energy surface generated from CCSD(T) calculations, as well as on the BLYP DFT potential energy surface sampled by means of the Car-Parrinello algorithm. The calculated spectra obtained with internal energies corresponding to a temperature of about 30 K are in overall good agreement with those from experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
69
2
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(80 citation statements)
references
References 37 publications
7
69
2
2
Order By: Relevance
“…[25][26][27] We note that the other fundamental vibrations found by AIMD in the fingerprint region as assigned by MCTDH show similar character. [9,31,33,34] However, tagging effects are found to be dramatic for the 1000 cm À1 proton-transfer mode (Figure 2 d).…”
supporting
confidence: 63%
See 1 more Smart Citation
“…[25][26][27] We note that the other fundamental vibrations found by AIMD in the fingerprint region as assigned by MCTDH show similar character. [9,31,33,34] However, tagging effects are found to be dramatic for the 1000 cm À1 proton-transfer mode (Figure 2 d).…”
supporting
confidence: 63%
“…The AIMD approach to theoretical vibrational spectroscopy [20][21][22][23] has been demonstrated specifically for bare H 5 O 2 + itself [24][25][26][27] to compare favorably with traditional approaches based on qualitative assessments. Herein, using AIMD trajectories, approximate normal modes are determined which supply a full set of optimized vibrational coordinates that represent the fundamental modes; [23,28] details are given in the Supporting Information.…”
mentioning
confidence: 99%
“…Extensive experimental [24][25][26][27][28] and theoretical [29][30][31][32][33][34][35][36][37] studies of an isolated Zundel cation in the gas phase have been conducted, most notably by means of vibrational spectroscopy [38,39], to probe its structure and the extent of the coupling between its constituent atoms. In both experimental and computational studies, the H/D isotopic substitution were found to significantly affect the intensity of infrared peaks of mixed H/D species [40,41].…”
Section: Together With the Eigen Cation H 3 Omentioning
confidence: 99%
“…[44] However, the AIMD results reveal a prominent temperature dependence for this spectral feature, [49,51] and hence it could be speculated that the temperature dependence of classical nuclear dynamics underlying such AIMD simulations may have hampered earlier studies [52][53][54][55] in reproducing (even qualitatively) the doublet feature. Studies on the influence of the messengers on the spectra additionally must deal with a sufficiently accurate description of the weak intermolecular interactions within the employed electronic structure method and, importantly, sufficient sampling of the vast phase space accessible to these floppy systems at finite temperature.…”
Section: Introductionmentioning
confidence: 95%
“…Despite the significant a priori approximations introduced by using approximate electronic structure theory ("on the fly") in conjunction with classical dynamics of nuclear motion, it has been demonstrated [49,51] that the AIMD approach to theoretical IR spectroscopy can qualitatively reproduce even the intricate doublet feature of bare H 5 O 2 + and its isotopologues compared to quasi-exact MCTDH calculations. [44] However, the AIMD results reveal a prominent temperature dependence for this spectral feature, [49,51] and hence it could be speculated that the temperature dependence of classical nuclear dynamics underlying such AIMD simulations may have hampered earlier studies [52][53][54][55] in reproducing (even qualitatively) the doublet feature.…”
Section: Introductionmentioning
confidence: 99%